(3WHbGJ GdMfGjdgs - (3GdbGVi CHi GdMSjf eMeO Hf eMeO Hf GdMSjf CHi jYdj GdMfHdi GdaQGAs; (3YHO GdQMef Hf CMeO Hf QLH GdSGdej GdHZOGOj GdMfHdj, Rjf GdOjf CHj GdaQL,J (B795 (3g` s ((3YHOGdbGOQ Hf YHOGdeDef GdbQTi s)
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdYXje s
(3BNQgG (B:s
(3hMSHfG Gddg hfYe Gdhcjd s
(3LYd GdeDda gPg GdWHbGJ Ydi SJ WHbGJ GdChdi hGdKGfjI Ydi MQha GdeYLe heG HYOgG Ydi JbOje GdYeQ hGdhaGIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B557 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B167 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1097s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs